Qualitative exploration of the challenges and the benefits of the nursing process in clinical practice: A study among registered nurses in a municipal hospital in Ghana - Timothy Gazari; Felix Apiribu; Richard Adongo Afaya; Atanuriba Gideon Awenabisa; Veronica Millicent Dzomeku; Adwoa Bemah Boamah Mensah; Philemon Adoliwine Amooba; Margaret Wekem Kukeba (Wiley, 2021)
Abstract Aim This study aims to explore the challenges and benefits of using the nursing process in a Ghanaian Hospital. Design The study employed a qualitative descriptive design to explore the challenges and the benefits of the utilization of the nursing process. Methods Twelve (12) Registered Nurses were recruited for the study using purposive sampling. Recorded in‐depth interviews were conducted and data were analysed using thematic analysis. Results The study found a low nurse‐to‐patient ratio, inadequate knowledge, apathy, inadequate logistics, poor supervision as challenges. However, quality and cost‐effective care improved nurse-patient relationships, and job satisfaction was found to be the benefits of nursing process use. Interventions to improve its utilization should be targeted towards improving the nurse‐to‐patient ratio, provision of adequate resources and inclusion of the nursing care plan in patient folders.